Breviscapine Blunts Hypertrophic Scar Formation via Dual Suppression of TGF-β1 Signaling and the Akt-mTOR Pathway - Peng Guo; Qianqian Gao; Li Lin (Discovery Medicine, 2026)
Background: Hypertrophic scar (HS) arises from aberrant cutaneous wound healing, characterized by uncontrolled myofibroblast proliferation and disproportionate extracellular matrix (ECM) accumulation. Breviscapine, a natural compound, suppresses inflammation and fibrosis. This study aimed to evaluate breviscapine as a therapeutic avenue against HS and unravel its molecular basis. Methods: In vivo, a rabbit ear HS model was established and treated with different doses of breviscapine. Scar morphology was macroscopically evaluated. Fibrosis-related markers (collagen type I alpha 1 [COL1A1], collagen type III alpha 1 [COL3A1], actin alpha 1, skeletal muscle [ACTA1], alpha-smooth muscle actin [α-SMA]) were quantified by quantitative real-time PCR (qRT-PCR) and Western blotting. α-SMA expression, collagen fiber organization and transforming growth factor-β1 (TGF-β1) levels were assessed by immunofluorescence staining, Masson staining, and immunohistochemistry/Western blotting, respectively. In vitro, HS fibroblasts (HSFs) were exposed to breviscapine, and cell counting kit-8 (CCK-8) assay, Sirius red staining and Western blotting were separately performed to determine cell viability, collagen production, and the expression of fibrosis-related markers, TGF-β1, and the Akt-mTOR pathway. Results: In vivo, breviscapine treatment attenuated rabbit ear scar formation, while diminishing COL1A1/COL3A1/ACTA1 mRNA levels and collagen I/collagen III/α-SMA/TGF-β1 protein levels and improving collagen fiber density and arrangement (p < 0.001). In vitro, breviscapine inhibited HSF viability, reversed TGF-β1-stimulated collagen overproduction, and suppressed the protein expression of fibrosis-related markers (p < 0.05). Notably, breviscapine attenuated the protein expression of TGF-β1 and the Akt-mTOR pathway in HSFs (p < 0.01). Conclusion: Breviscapine exerts anti-HS effects by targeting the TGF-β1 signaling and the Akt-mTOR pathway, providing a novel natural therapeutic candidate for HS management with anti-fibrotic, anti-proliferative, and pathway-targeted effects. Further investigation is warranted to validate its efficacy in clinical settings and to explore its long-term safety and optimal delivery strategies.